2021
DOI: 10.1080/21655979.2021.2001168
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA NR2F1-AS1 plays a carcinogenic role in gastric cancer by recruiting transcriptional factor SPI1 to upregulate ST8SIA1 expression

Abstract: Gastric cancer (GC) is a highly malignant solid tumor of the digestive tract, which is associated with a high mortality rate. Long non-coding RNA (lncRNA) nuclear receptor subfamily 2 group F member 1 antisense RNA 1 (NR2F1-AS1) has been reported to exert a tumor-promoting effect in some types of cancer. The present study aimed to investigate the role of NR2F1-AS1 in GC. The expression levels of NR2F1-AS1 and its potential target gene were measured in GC cell lines. Bioinformatics analysis, an RNA immunoprecip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…In this study, we found that SPI1 is an important regulator of MES phenotype transition and maintenance in GSCs. Similarly, previous studies have shown the potential role of SPI1 in the MES transition in gastric cancer [18], colorectal cancer [19], and non-small-cell lung cancer [16]. This underscores the recognized correlation between MES transition, stemness acquisition, invasiveness, treatment resistance, and metastasis.…”
Section: Fkbp12 Plays a Regulatory Role In Spi1-induced Tgf-β1-pi3k-a...supporting
confidence: 77%
“…In this study, we found that SPI1 is an important regulator of MES phenotype transition and maintenance in GSCs. Similarly, previous studies have shown the potential role of SPI1 in the MES transition in gastric cancer [18], colorectal cancer [19], and non-small-cell lung cancer [16]. This underscores the recognized correlation between MES transition, stemness acquisition, invasiveness, treatment resistance, and metastasis.…”
Section: Fkbp12 Plays a Regulatory Role In Spi1-induced Tgf-β1-pi3k-a...supporting
confidence: 77%
“…However, the specific mechanism needs further research and verification. Previous studies found that NR2F1-AS1 upregulates the expression level of ST8SIA1 by recruiting SPI1, thereby promoting proliferation and metastasis of BCa cells ( 33 ). LINC00649 has verified its tumor-promoting effect in gastric cancer, colorectal cancer, BCa, etc ( 34 36 ).…”
Section: Discussionmentioning
confidence: 97%
“…Coincidentally, upregulation of SPI1 has been reported in ESCC and correlated with M2 macrophage maintenance [ 37 ]. The transcription regulation of SPI1 on the downstream targets in several cancer cases has been reported to involve lncRNAs [ 26 , 27 ]. The lncRNAs are over 200-nt noncoding RNAs fulfilling key functions in governing chromatin dynamics, gene expression, growth, differentiation, and development of cancer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the regulation of SPI1 on the transcription of molecular substrates in several cancer cases has been reported to involve lncRNAs [ 26 , 27 ]. We wondered if any lncRNA holds accountable for the SPI1-mediated SIGLEC9 activation in TAMs.…”
Section: Radiotherapy Induces Phenotype Change Of Tamsmentioning
confidence: 99%